Evaluation of the Association between Unhealthy Lifestyle and Colon Cancer among the Patients Treated in the Oncology Unit of Benghazi Medical Center - S. Baiu , Heithum; A. Bendardaf , Salha; A. Abdel Salam , Areej; A. Elmogrbi, Nafessa; S. Hefter, Anwaar; S. E. Imbarak , Marwa (Libyan Journal of Public Health Practices, 2024)
Colorectal cancer is one of the most common types of cancer around the world and is related to an unhealthy lifestyle. A retrospective case-control study, of 95 colorectal cancer patients and 95 matched controls investigated the association between lifestyle factors and colorectal cancer at Benghazi Medical Centre from June to July 2024. Data were collected via interviews and questionnaires. A binary logistic regression test was used to evaluate the relationship between each lifestyle variable and colon cancer. BMI was statistically significantly related to colon cancer (P = 0.045; odd ratio = 0.927, 95% CI (0.861 to 0.998)). Several dietary factors showed significant associations with colon cancer risk. Healthy diets were inversely associated (OR 0.379, P = 0.045), while vegetable consumption was positively associated (OR 4.619, P = 0.001). Red meat consumption also showed a positive association (OR 2.479, P = 0.042), whereas increased sugar consumption was inversely associated (daily: OR 0.243, P = 0.007; >daily: OR 0.222, P = 0.004). Adoption of health education interventions by health educators in Libya to promote healthy lifestyles is recommended. Future studies will be needed for further evaluation of the relationship between lifestyle factors and colorectal cancer in Libya.